Pemberdayaan UMKM dalam Meningkatkan Penjualan Industri Teh di Kota Bekasi - Tri Nurmayanto; Sri Sutani Bani; Siti Nurjannah Sanusi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Community empowerment is one of the indicators that need to be fostered in an effort to improve and support the acceleration program for village independence development. The purpose of this activity is for UMKM actors to be able to develop their businesses and become elements of success in supporting community independence. The partners themselves are the Jatirahayu Village community, the Jatirahayu Village government, Pondok Melati District, Bekasi City. The implementation of this community service itself will involve the Head of the Village and staff of Jatirahayu Village, lecturers at STIE Widya Persada, and students of STIE Widya Persada Community service partners are UMKM in Jatirahayu Village, Bekasi City. The number involved is 13 people, the data collection technique used in this study is the Socialization method, interviews, and documentation and evaluation using questionnaires. Overall, the percentage of partner understanding is 80% or equivalent to 10 Partners. The results achieved are an increase in the professionalism of UMKM actors which has an impact on increasing community income